CYBERBULLYING SEBAGAI DAMPAK NEGATIF PENGGUNAAN TEKNOLOGI INFORMASI - flourensia sapty rahayu (Faculty of Computer Science Universitas Indonesia, 2012)
Information Technology can bring postive and negative impacts to our lives. One of the negative impact that emerge with the this technology development is Cyberbullying. Cyberbullying is any cyber-communication or publication posted or sent by a minor online, by Information Technology devices that is intended to frighten, embarrass, harass, hurt, set up, cause harm to, extort, or otherwise target another minor. In other countries there are many cases of Cyberbullying that ended with very serious event such as the suicide of the victims. This study was conducted to gain insight into how this phenomenon occur in Indonesia. We used questionnaires as a mean to get the informations about Cyberbullying among Indonesian teenagers. We distributed these questionnaires to secondary and high school students in Magelang, Yogyakarta and Semarang. The result shows that Cyberbullying has already happened with a big enough number (28%) but the impact was not very serious. From the answers we can conclude that many teens haven’t understand what Cyberbullying is and what its potential dangerous impacts may follow. We also explored the roles, responsibilities, and things that can be done by teens, parents, schools, law enforcements, and communities in order to prevent and stop Cyberbullying.